Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am trying to get the particular solution to the equation -

$y''' + 4y'' + 5y' + 2y = e^{-t} $

We are taught the method of undetermined coefficients to solve such equations. However, one of the solutions of the homogenous equation is of the form of the particular equation (so when I substitute it, I get LHS$ = 0$, while RHS is not $0$ ).

Please give me a hint on how should I proceed to get the particular solution.

[This question is a part of the tricky questions set given to us. The actual differential equation is a bit more complicated, but I have reduced it to the point I have got stuck in.]

share|improve this question
add comment

2 Answers 2

up vote 5 down vote accepted

Since $P(D)y=(D+1)^3(D+2)y=0$ so your particular solution is $$y_p=At^2e^{-t}$$ where $A$ is an unknown constant. Note that the differential operator $D^n$ annihilates each of the functions: $$1,t,t^2,...,t^{n-1}$$ and differential operator $(D-\alpha)^n$ annihilates each of the following functions: $$e^{\alpha t},te^{\alpha t},t^2e^{\alpha t},...,t^{n-1}e^{\alpha t}$$

share|improve this answer
    
Thanks for help. I think , the equ is $P(D)y=(D+1)^2(D+2)y=0$. Will the solution still be one you gave above? –  Guanidene Sep 3 '12 at 9:12
    
In fact, $P(D)y=(D+1)^2(D+2)y=e^{-t}$, but if you take $(D+1)$ one more time of both sides; you get mine. :-) –  B. S. Sep 3 '12 at 9:16
    
Ok. Thanks. Didn't think about that! :) –  Guanidene Sep 3 '12 at 9:19
    
Always a good teacher! +1 –  amWhy Mar 14 '13 at 2:05
add comment

Perhaps this will grant some insight. In a way, the left hand side can be factored like a polynomial. So just as

$s^3+4s^2+5s+2=(s+1)(s^2+3s+2)$

if you let $u=y''+3y'+2y$, this equation can be rewritten as

$y'''+4y''+5y'+2y=(y''+3y'+2y)'+y''+3y'+2y=u'+u=e^{-t}$

So let's solve this for $u$ using integrating factors.

$u'e^t+ue^t=(ue^t)'=1$

$ue^t=t+C,u=y''+3y'+2y=te^{-t}+Ce^{-t}$

If, as you put it, this solution of the homogenous equation had not been of the form of the particular equation, the right side before integration would have been of the form $e^{nt}$. Instead, we've had a $te^{-t}$ term introduced.

Something similar will occur when we make the substitution $v=y'+2y$, where we will again have $e^t$ as an integrating factor.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.